Incorporation of non-canonical amino acids into the developing murine proteome - Calve, Sarah (Sci Rep, 2016)
Analysis of the developing proteome has been complicated by a lack of tools that can be easily employed to label and identify newly synthesized proteins within complex biological mixtures. Here, we demonstrate that the methionine analogs azidohomoalanine and homopropargylglycine can be globally incorporated into the proteome of mice through facile intraperitoneal injections. These analogs contain bio-orthogonal chemical handles to which fluorescent tags can be conjugated to identify newly synthesized proteins. We show these non-canonical amino acids are incorporated into various tissues in juvenile mice and in a concentration dependent manner. Furthermore, administration of these methionine analogs to pregnant dams during a critical stage of murine development, E10.5–12.5 when many tissues are assembling, does not overtly disrupt development as assessed by proteomic analysis and normal parturition and growth of pups. This successful demonstration that non-canonical amino acids can be directly administered in vivo will enable future studies that seek to characterize the murine proteome during growth, disease and repair.